Гамартія і катарсис в класичній грецькій та шекспірівській трагедії - Колесник, О.С. (Культура народов Причерноморья, 2013)
В статті порівнюється розуміння гамартії та катарсису в античній трагедії та в
трагедіях В.Шекспіра. Демонструється осмислення сутності катарсису та формулювання його
незалежного від аристотелівського визначення в тексті «Короля Ліра».
Ключові слова: Аристотель, гамартія, губріс, катарсис, трагедія, Шекспір. В статье
сравниваются понимания гамартии и катарсиса в античной трагедии и в трагедиях В.Шекспира.
Демонстрируется осмысление сущности катарсиса и формулирование его независимого от
аристотелевского определения в тексте «Короля Лира». The author
compares the understanding of hamartia and catharsis in the Classical Greek tragedy and in the works of
W.Shakespeare. It is shown that Shakespearean tragedy was not greatly influenced by the Classics, and
demonstrates quite different poetics. At the same time, there are numerous parallels between the two types of
tragedy, that make the comparison productive. There are different views as to the extent of the tragic flaw of the
heroes, and even as to the existence of such a flaw. So, at least in Shakespearian tragedy, in many cases it is
better to define hamartia as a mistake of wrong choice, than as a character deficiency. In the text of
Shakespeare’s “King Lear” we see not only the search for the Cosmic laws, governing the natural, social and
personal interrelations, but also the finding of such formulae. One of them can be regarded as a definition of
catharsis with the emphasis on the ethical component of this complex phenomenon.
Key words: Aristotle, catharsis, hamartia, hubris, tragedy, Shakespeare.